Family violence and therapeutic intervention management by the Ministerio de la Mujer y Poblaciones Vulnerables [Ministry of Women and Vulnerable Populations] - Reyes Castillo, Eduardo Antonio (2022)
This paper addresses the connection between family violence and therapeutic intervention management by the Ministry of Women and Vulnerable Populations. Experiences and good practices will be addressed through systematic and historical-analytic-synthetic methodologies to promote proper management and implementation of therapeutic interventions in cases of family violence, in order to contribute effectively to the empowerment and intervention in violence against women and members of a family group.